Analisis Efektivitas Metode Injeksi Dalam Inokulasi Jamur Tiram (Pleurotus Ostreatus) di Cv. Budidaya Jamur Sejati - Fitriyani, Lailatul; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Oyster mushroom (Pleurotus ostreatus) cultivation is a rapidly growing agribusiness sector in Indonesia. One important stage is inoculation, namely planting seeds into the growing medium. Commonly used manual methods have weaknesses such as uneven seed distribution and a high risk of contamination. This study aims to analyze the effectiveness of the injection inoculation method compared to the manual method at CV. Budidaya Jamur Sejati. The research methods include observation, field practice, interviews, and documentation during street vendor activities. The parameters observed include the speed of mycelium colonization, inoculation success rate, number of fruiting bodies, and harvest weight. The results showed that the injection method was superior with a faster colonization time (12–14 days), a success rate reaching 95%, and an increase in the number of fruiting bodies and an average harvest weight of 350–400 grams per baglog. Thus, the injection method is considered more effective and efficient, and has the potential to increase the productivity and quality of oyster mushroom cultivation results.